2020
DOI: 10.21203/rs.3.rs-44378/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Guidance for overviews of reviews continues to accumulate, but important challenges remain: A scoping review

Abstract: Background. Overviews of reviews (overviews) provide an invaluable resource for healthcare decision-making by combining large volumes of systematic review (SR) data into a single synthesis. The production of high-quality overviews hinges on the availability of practical evidence-based guidance for conduct and reporting.Objectives. Within the broad purpose of informing the development of a reporting guideline for overviews, we aimed to provide an up-to-date map of existing guidance related to the conduct of ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…There are several ways to deal with overlap at different stages during the development of the overview. [8][9][10][11] Overview authors may decide about eligibility, data extraction, risk of bias assessment and synthesis/ presentation of the results, based on the overlap of primary studies among the included SRs. Indeed, a variety of tools has been proposed for guiding these decisions.…”
Section: Methods and Issues When Assessing Overlapmentioning
confidence: 99%
“…There are several ways to deal with overlap at different stages during the development of the overview. [8][9][10][11] Overview authors may decide about eligibility, data extraction, risk of bias assessment and synthesis/ presentation of the results, based on the overlap of primary studies among the included SRs. Indeed, a variety of tools has been proposed for guiding these decisions.…”
Section: Methods and Issues When Assessing Overlapmentioning
confidence: 99%
“…This was supplemented by a study examining the completeness of reporting in a random sample of more contemporary overviews (published between January 2015 and March 2017) (18). The second was a scoping review of methodological guidance and author-reported challenges related to conducting overviews of reviews (14). We continued to monitor article alerts (i.e., Google Scholar, Scopus Citing References, and PubMed Similar Articles) until publication of the reporting guideline to keep apprised of new developments that could impact its content.…”
Section: Step 2: Evidence Reviews and Development Of The Initial Chec...mentioning
confidence: 99%
“…The PRIOR statement is intended for overviews of reviews of healthcare interventions and may not be applicable to other fields and/or other types of overviews of reviews (e.g., qualitative, diagnostic accuracy). The guideline is based on currently available evidence regarding the reporting of published overviews (30), a scoping review of currently available methodological guidance (14), and other recent evidence maps regarding the methods used in overviews of reviews (15,16). We acknowledge that for some items, there is little or no methodological guidance available for overview of reviews authors (e.g., the adaptation of GRADE to overviews, the assessment of missing results in a synthesis), and that in time PRIOR will require an update.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations